2020
DOI: 10.2147/cpaa.s234227
|View full text |Cite
|
Sign up to set email alerts
|

<p>Determination of the Permeation and Penetration of Flurbiprofen into Cadaveric Human Pharynx Tissue</p>

Abstract: Objective: Flurbiprofen 8.75 mg spray and lozenge have a rapid onset of action for sore throat relief, suggesting local action, although tissue penetration and the mechanism of local relief have not been determined. This investigation aimed to quantify the permeation and penetration of flurbiprofen, applied as local pharmaceutical forms, into full-thickness cadaveric human mucosal pharynx tissue, representing the clinical scenario as far as possible. Methods: A validated high-performance liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
3
0
5
Order By: Relevance
“…This study reaffirmed the findings of our previous study, which demonstrated that flurbiprofen from a throat spray solution and a dosing solution prepared from a lozenge formulation is capable of penetrating the pharynx tissue, 24 while allowing visualization of radiolabeled flurbiprofen penetration across all layers of the pharynx tissue. Radiolabeled flurbiprofen was detected in the deepest sections of the human cadaveric pharynx tissue.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study reaffirmed the findings of our previous study, which demonstrated that flurbiprofen from a throat spray solution and a dosing solution prepared from a lozenge formulation is capable of penetrating the pharynx tissue, 24 while allowing visualization of radiolabeled flurbiprofen penetration across all layers of the pharynx tissue. Radiolabeled flurbiprofen was detected in the deepest sections of the human cadaveric pharynx tissue.…”
Section: Discussionsupporting
confidence: 89%
“…15 This effect is considered to be due to the local absorption which has been previously demonstrated through the buccal mucosa and ex vivo cadaveric human pharynx tissue. [21][22][23][24] This research builds on a previous study, which involved the development of a method to quantify permeation and penetration of flurbiprofen through the human pharynx tissue in an ex vivo model using a Franz diffusion cell method, 25 followed by quantification of the permeation and penetration of flurbiprofen in the human pharynx tissue, 23,24 and development of a model to replicate absorption from lozenge and throat spray using a Franz diffusion cell.…”
Section: Introductionmentioning
confidence: 99%
“…Sore throat refers to the pain caused by inflammation of tissues located behind the throat, 44 and up to 80% of the cases is caused by viruses (eg, coronavirus, influenza, and rhinovirus). 45 , 46 Internationally, sore throat complaints account for 1–4% of all primary care reports.…”
Section: Sore Throatmentioning
confidence: 99%
“…в 2020 г. с помощью метода высокоэффективной жидкостной хроматографии и модели микроклеток Франца смогли количественно оценить проникновение флурбипрофена в ткани глотки человеческого трупа. Была доказана способность флур бипрофена проникать во все слои слизистой оболочки глотки, включая подлежащую пластинку собственной оболочки с кровеносными сосудами и нервными волокнами [34].…”
Section: Infections In Otorhinolaryngologyunclassified